The Legal and Institutional Challenges to the Implementation of the R2P Principle - Onu, Kingsley Osinachi (ABUAD Law Journal, 2019)
The Responsibility to Protect (R2P) is an international legal principle that places both general and customary international law obligation on States to protect their own citizens from mass atrocity core crimes of genocide, war crimes, crimes against humanity and ethnic cleansing. This paper adopts doctrinal research method in examining the legal and institutional challenges to the global implementation of the R2P principle. This paper finds that there exist some teething legal and institutional challenges that affect the effective implementation of the principle.Implementation has been mixed as the case studies shows. Where it had been implemented, as in Libya, the result was quite limited while in situations where it has not been implemented at all, as in Syria, it calls to question the genuineness and integrity of the legal, political and moral commitment of the international community of States to end atrocious crimes in many troubled regions of the world.Conclusively, the R2P principle is an emerging customary rule of international law but has yet to attain full status of “jus cogens” peremptory norm of international law.The paper therefore recommends that an advisory body be established by the United Nations to advise States on the limitation of the R2P principle. It is also recommended that building institutional capacity and preparedness by States backed by greater cooperation between States, the international community and international organizations to implement the R2P principle is central to guaranteeing an effective R2P regime that is properly implemented in a timely manner. It also recommends measures to remove the legal and political uncertainties surrounding the outer bounds and limits of the principle arguing for inclusion of environmental crimes and natural disasters as grounds for invocation of R2P.